Prevalence of methicillin and vancomycin-resistant Staphylococcus aureus in goat meat and environment of sales in Uyo metropolis, Akwa Ibom State, Nigeria - E. Akpanenang, Edet; G. Asuquo, Ememobong; E. Udobi, Chinweizu; N. Nwosu , Chibuzor; D. Onele, Ugochukwu (Nigerian Journal of Pharmaceutical and Applied Science Research, 2024)
Background: There has been an increasing incidence of drug resistance associated with Methicillin-Resistant Staphylococcus aureus (MRSA) and the emergence of vancomycin resistance trait in humans leading to concerns to detect other sources which this resistant could emanate. This study was carried out to determine the prevalence, antibiotic susceptibility profile of MRSA and vancomycin-resistant Staphylococcus aureus (VRSA) in goat meat, its handlers and environment of sales within Uyo Metropolis, Akwa Ibom State. Methods: Staphylococcus aureus were isolated from the samples using mannitol salt agar (MSA) and standard laboratory methods. Antibiotic susceptibility pattern was determined using modified Kirby Bauer disc agar diffusion method. Results: Ninety-five (63.3%) isolates out of the 150 samples were confirmed and characterized as Staphylococcus aureus. One hundred percent (100 %) of the isolates were resistant to norfloxacin (10 µg), One hundred percent (100 %) were susceptible to rifampicin (20 µg) and levofloxacin (20 µg) respectively. Fifty-two (54.7 %) of the isolates were MRSA. The multiple antibiotics resistance (MAR) index indicated that 39 (75 %) were resistant to 3 or more antibiotics (MARI ? 3). Further PCR analysis of Staphylococcus aureus isolates that were MRSA indicated the presence of mecA gene in all the samples screened. There was a hundred percent (100 %) susceptibility of confirmed MRSA to vancomycin. Conclusion: Goat meat, its environment of slaughter and sales in Uyo metropolis were confirmed a reservoir of Methicillin-Resistant Staphylococcus aureus (MRSA) but not of Vancomycin-Resistant Staphylococcus aureus (VRSA).